2000
DOI: 10.1002/1521-3935(20000801)201:12<1317::aid-macp1317>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Solid state photopolymerization of modified amphiphilic diynes in multilayers

Abstract: Solid state topochemical photopolymerization of amphiphilic diynes modified at hydrophobic part of molecule was under the study. All compounds formed stable monomer monolayers on an aqueous subphase surface and were transferred as multilayers onto quartz substrates by the Langmuir‐Blodgett technique. The changes of the multilayer absorption spectra as a function of UV irradiation time have been investigated. It is shown that the insertion of an ester or sulfonyl group into the hydrophobic part of the diyne mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Photopolymerization in the solid state is a powerful method to afford polymers with controlled topochemical structure 62. 63 Because it is easy to adsorb the monomers in a sonicated suspension where the crystals are all separate, the contact area is then a minor issue.…”
Section: Third Stage Of Organizationmentioning
confidence: 99%
“…Photopolymerization in the solid state is a powerful method to afford polymers with controlled topochemical structure 62. 63 Because it is easy to adsorb the monomers in a sonicated suspension where the crystals are all separate, the contact area is then a minor issue.…”
Section: Third Stage Of Organizationmentioning
confidence: 99%
“…Die Photopolymerisation in Feststoffen ist eine erfolgreiche Methode zur Herstellung von Polymeren mit einstellbarer topochemischer Struktur 62. 63 Da es einfach ist, Monomere in Suspensionen zu adsorbieren, sodass die Nanokristalle gut getrennt sind, ist die Kontaktfläche unkritisch.…”
Section: Dritte Organisationsstufeunclassified
“…The limit area per molecule, extrapolated to zero surface pressure by the linear isotherm portion, was 0.54 nm 2 /mol. We note that the blue form almost was not observed previously during photopolymerization of alcohol derivatives of diacetylene, and the red form of PDA was immediately formed, while isotherms of diin derivatives under study showed a comparatively rapid increase in the surface pressure in the formed Langmuir monolayer with decreasing area per molecule [28,29]. The latter situation could lead to rapid monolayer formation, which did not allow individual monomer molecules to occupy more advantageous positions for achieving well ordered film structures.…”
mentioning
confidence: 52%